Synergetic enhancement toxicity of copper, cadmium and microcystin-LR to the Ceratophyllum demersum L. (30th October 2020) - Cao, Qing; Liu, Weijing; Gu, Yurong; Xie, Liqiang; Jiang, Weili; Gao, Yan; Yang, Liuyan
Abstract: Heavy metals and microcystins commonly co-exist in water bodies with cyanobacteria, and have been shown to affect aquatic plants. However, their combined effects remain largely unknown. In this study, the toxic effects of copper (Cu) and cadmium (Cd) on Ceratophyllum demersum L. were characterized in the presence of microcystin-LR (MC-LR). The results showed that the bioaccumulation of MC-LR and Cu/Cd in C. demersum was significantly increased by the interaction between MC-LR and Cu/Cd. The combined toxicity assessment results suggested that the toxicities of Cu or Cd to C. demersum would be largely exacerbated by MC-LR, which could be the results of increased bioaccumulation of the pollutants. Cu, Cd and MC-LR, as well as their mixture, significantly decreased plant fresh weight and total chlorophyll content of C. demersum, especially at their high concentrations. The antioxidative system was activated to cope with the adverse effects of oxidative stress. Antioxidant enzyme activities were significantly stimulated by Cu, Cd and MC-LR, as well as their mixture. However, the decreased superoxide dismutase (SOD) and glutathione reductase (GR) activities were observed when exposed to relative high concentrations of Cu or Cd together with MC-LR of 5 μg L −1 . MC-LR brought more stress to the antioxidative system, which is another possible explanation for the synergistic effect. Our findings highlight increased ecological risks of the co-contamination of heavy metals and harmful cyanobacteria. Graphical abstract: Image 1 Highlights: First report on combined toxicity of microcystin-LR and cadmium on aquatic plants. Microcystin-LR increased copper and cadmium accumulation in C. demersum. Synergistic effects of microcystin-LR and copper/cadmium were observed.